2015
DOI: 10.1111/pde.12625
|View full text |Cite
|
Sign up to set email alerts
|

Dermatitis Artefacta in Childhood: A Retrospective Analysis of 44 Patients, 1976–2006

Abstract: Background: Dermatitis artefacta (DA) consists of self-inflicted skin lesions that the patient denies having produced. Objectives: To conduct a single-center retrospective clinical review of children and adolescents diagnosed with DA. Methods: From 1976 to 2006, data were collected on children diagnosed with DA who were seen in the Department of Dermatology in our hospital. Clinical and epidemiologic features are described. Forty-four children (mean age 12.9 yrs) were selected, representing 21.9% of the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…The dermatologic manifestation in our case is similar to superficial skin lesions in face and upper limbs as reported in literature. [ 8 ] Interpersonal conflicts with siblings and parent are often the underlying stressors as was in our patient. [ 4 5 ]…”
Section: Discussionmentioning
confidence: 83%
“…The dermatologic manifestation in our case is similar to superficial skin lesions in face and upper limbs as reported in literature. [ 8 ] Interpersonal conflicts with siblings and parent are often the underlying stressors as was in our patient. [ 4 5 ]…”
Section: Discussionmentioning
confidence: 83%
“…The other 14 patients (51.9%) declined psychiatric evaluation and were subsequently lost to follow-up. 11 In the second study looking at a subset of the 201 patients with DA, Alcántara Luna et al 13 identified paediatric patients diagnosed with DA over the same 30-year time period. There were 44 children and adolescents, with a mean age of 12.9 years.…”
Section: Resultsmentioning
confidence: 99%
“…Out of these patients, two had psychiatric diagnoses, including a personality disorder and history of suicide attempt. 13 A prospective study was carried out to investigate DA among members of the Israel Defence Force (IDF). Over a 3-year period, from 1997-2000, 14 soldiers were treated.…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective analysis of 44 pediatric patients with DA from 1976 to 2006, the most frequent clinical forms were excoriations, ulcers, and blisters, which were prominent in our case. 6 The appearance of DA lesions vary, and superficial erosion, hyperpigmented macules, excoriation, deep necrosis, crusts, and scars make up approximately 50%, 36%, 17%, 16%, 8%, and 7% of lesions, respectively. Overall, about 72% of the patients have 1 type of lesion morphology, while 41% have 2 types and 31% have 3 types.…”
Section: Discussionmentioning
confidence: 99%